Referendum debate riposte - Garry Coutts (Scottish Journal of Residential Child Care)
Mark Smith’s case for independence boils down to:• there is a distinct Scottish approach to social welfare• our ability to pursue this approach is compromised by Westminster• the devolution settlement (and anything short of full independence) will not allow this tradition to flourishPlacing the current debate in the context of policy development since the Reformation is an interesting approach. It certainly allows the author a wealth of material from which to pick examples. However, I query whether the historical record actually shows there is such a distinct cultural difference in social welfare policy as implied.